Clinicopathological and bacteriological investigation of chronic fowl cholera in commercial laying hens - Atria Destriana Fath; Armanda Dwi Prayugo; Popy Christin Ziliwu; Rocky Silvester; Sarasati Windria; Tyagita Hartady; Ita Krissanti; Faisal Amri Satrio (ARSHI Veterinary Letters, 2026)
Fowl cholera, caused by Pasteurella multocida, remains a major threat to poultry health and productivity. This case study identified the etiological agent associated with clinical disease and gross lesions in laying hens from a commercial farm in Sumedang, West Java, Indonesia. The investigations included necropsy, bacterial culture, Gram staining, and biochemical characterization. Affected birds showed torticollis, conjunctivitis, mild wattle and comb swelling, respiratory rales, reduced feed intake, decreased egg production, greenish-white diarrhea, and lethargy. Necropsy revealed hemorrhagic lesions in the trachea, lungs, and intestinal mucosa, with absent developing ovarian follicles. Culture on blood and chocolate agar produced whitish-gray translucent colonies. Gram staining showed Gram-negative coccobacilli singly or in pairs. Biochemical findings supported the identification of P. multocida. Overall findings were consistent with chronic fowl cholera and underscored the importance of vaccination, biosecurity, and early surveillance to limit economic losses in commercial layer farms.